An Investigation of Seventh Grade Students’ Performances on Conceptual, Procedural and Graphical Problems Regarding Circles - İncikabı, Lütfi; Biber, Abdullah; Takıcak, Mujdat; Bayam, Semiha (Ninety Nine Publication, 2015)
The purpose of this study is to determine seventh grade students’ preferences among the procedural, conceptual and graphical questions in the subject of circles, to define their success levels in their preferences, and to compare students’ success levels in one question type with their performances in other question types. The methodology adopted during this research was case study. Based on criterion-based purposive sampling strategy, 98 middle school students were selected as the participants. Data were collected through an achievement test consisting of nine questions (three per question type). The results obtained from the study indicated that students mostly preferred graphical question types. Moreover, majority of students could not succeeded high levels in their preferred question types. In addition, the students performed better in graphical question types; however, the failure in procedural question types was remarkable. Keywords: Multiple representations, middle school students, mathematics education, circles
Keywords: Alan Eğitimleri; Multiple representations; middle school students; mathematics education; circles; Other Fields of Education; 4. Education